PEMBELAJARAN DENGAN MEDIA POHON LITERASI UNTUK MENINGKATKAN KEMAMPUAN LITERASI PESERTA DIDIK KELAS I SDN SIDOREJO I TUBAN PADA TEMA PERISTIWA ALAM DAN SUBTEMA BENCANA ALAM - Siti Nurhayati; Anggun Winata (FKIP Unirow Tuban, 2018)
Literasi be one benchmark to determine the quality of education and human resources of a country. Indonesia compared to other Asian countries is included in the sequence below related to literacy. Accordingly, one of the primary schools in Tuban Regency, SDN Sidorejo I has low literacy skills. This is obtained from the result of literacy ability on prasiklus with an average of 13.5. The study aimed to improve literacy ability with tree literasi. Literature tree is chosen because it can build the creativity of learners that includes the power of thought and creativity, and motivate students to always read. In addition, the literacy tree is very simple and easy to implement. Literate trees are expected to improve the literacy ability of learners. This research is the Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of four phases of activity: (1) planning, (2) action, (3) observation, and (4) reflection. The subjects were students of class I SDN Sidorejo I Tuban Semester II Academic Year of 2017/2018. The instruments used in the research are syllabus, learning implementation plan, observation sheet, and literacy skill test. Based on the results of research and data analysis, it can be concluded that the literacy of students in grade I SDN Sidorejo I Tuban has increased with the media literasi tree. In prasiklus, participants' literacy skills are said to have a low category with an average of 13.5. In cycle I, literacy ability of participants is said to have low category with average is 39,2. In cycle II, literacy ability of participants is said to have medium category with average is 55.